SA-16 Blood Transfusion Importance in the Healing Process of Feline Panleukopenia Leading to DIC (Disseminated Intravascular Coagulation) - Kemala Sherlin; Eva Zulfiati; Belinda Martin (Hemera Zoa, 2018)
INTRODUCTIONFeline panleukopenia caused by feline parvovirus (FPV), which is a highly contagious virus affecting all members of Felidae. Severity of clinical signs depends on age, immune status, and concurrent infections. The severity of the disease varies from the subclinical to sudden death. Typical initial signs include fever, depression, and anorexia. Cats can initially present vomit with lower frequency, develop watery to hemorrhagic diarrhea. Atypical presentations are common, especially in adult cats. Infected cats die from complications associated with secondary bacterial infection, sepsis, dehydration, and disseminated intravascular coagulopathy (DIC). Mortality rates of 25%-90% in acute panleukopenia and up to 100% in per acute infections have been reported.